Loss of GLUT4 Induces Metabolic Reprogramming and Impairs Viability of Breast Cancer Cells. Issue 1 (January 2015) - Garrido, Pablo; Osorio, Fernando G.; Morán, Javier; Cabello, Estefanía; Alonso, Ana; Freije, José M.P.; González, Celestino
<x xml:space="preserve">Abstract</x> Metabolic reprogramming strategies focus on the normalization of metabolism of cancer cells and constitute promising targets for cancer treatment. Here, we demonstrate that the glucose transporter 4 (GLUT4) has a prominent role in basal glucose uptake in MCF7 and MDA‐MB‐231 breast cancer cells. We show that shRNA‐mediated down‐regulation of GLUT4 diminishes glucose uptake and induces metabolic reprogramming by reallocating metabolic flux to oxidative phosphorylation. This reallocation is reflected on an increased activity of the mitochondrial oxidation of pyruvate and lower lactate release. Altogether, GLUT4 inhibition compromises cell proliferation and critically affects cell viability under hypoxic conditions, providing proof‐of‐principle for the feasibility of using pharmacological approaches to inhibit GLUT4 in order to induce metabolic reprogramming in vivo in breast cancer models. J. Cell. Physiol. 229: 191–198, 2014. © 2014 Wiley Periodicals, Inc.